Self-assembled lanthanide-based helixes: synthetic control of the helical handedness by chirality of the ligand. Issue 1 (13th December 2021) - Wu, Min-Yu; Xu, Jing-Xiang; Chen, Yi-Hsin; Lu, I-Chung; Han, Jeng-Liang; Lin, Po-Heng
Abstract : Chiral lanthanide chains with a helical metal arrangement were synthesized and the helical handedness can be derived from chirality transfer of the ligands. Abstract : The control of the self-assembly of lanthanide helical chain and their helical handedness have been investigated for the first time. Δ- and Λ-form lanthanide chain complexes were obtained by introducing thiazolidine ligands that were synthesised from l - and d -cysteine, respectively, and shared the same formula: [Ln2 (L)3 (H2 O)5 ]∞ ·3H2 O (Ln: Sm and Eu) (L: 2-(2-hydroxy-3, 5-dinitrophenyl)thiazolidine-4-carboxylic acid). The crystallographic, circular dichroism, and luminescence properties of these novel lanthanide chain complexes were studied.